Energy Transmission to Long Waves Generated by Instantaneous Ground Motion on a Beach - Bandyopadhyay, Arghya; Mandal, Avijit (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Historically speaking, all high frequency earth-quakes do not produce tsunami which is evident from several earthquakes that took place in Indian Ocean between 2004 and 2006. The works of Geist et.al [’06] and Ammon et.al [’05] are good examples of such study through which they have also pointed out the miserable failures of the existing warning system. The reasons of no-generation of tsunami due to large quakes may be several but in this article we have tried to throw some light on this puzzle and tried to analyze energy transmission to a tsunami motion at steady state and have shown that no energy transmits for certain frequencies of the forcing parameter. We discuss here tsunami waves which are generated instantaneous bottom dislocation where the ocean floor is taken to be of variable slope and analytical solutions are provided correct to all time t.